Characteristics of peripheral blood stem cells: 2D-Gel electrophoresis and kinetic parameter of exocytosis - Jiraporn Kantapan (2018)
© 2016 Bentham Science Publishers. Background: Peripheral blood stem cells (PBSCs) are now established curative treatment for patients with various hematologic malignancies and are proposed to be superior to other cell sources for cell based therapy. Aims: The aims are to characterize the PBSCs by constructing proteome using 2D-gel electrophoresis and analyze the kinetic parameters of pirarubicin transport of PBSCs compared with peripheral blood mononuclear cells (PBMCs), and erythromyelogenous leukemic (K562 and K562/adr) cells. Methods: Whole cell proteomes of PBMCs, PBSCs and erythromyelogenous leukemic cells were separated by 2D-gel electrophoresis and analyzed by multivariate and principle component analysis. The parallel series of experiments were measured by pirarubicin transport parameters by the cells using spectrofluorometer. Results: The PBSCs were initially found in 1% in the fraction of PBMCs and majority of them were found in the culture after 14 days. Multivariate and principle component analysis revealed the proteins that might be considered as biomarkers of PBSCs (4 proteins), PBMCs (9 proteins), K562 (4 proteins) and K562/adr (9 proteins) cells. The analysis of transport of pirarubicin by these cell models indicated that PBSCs and PBMCs possessed exocytotic pathway by which the mean rate constant was equal to 0.056 ± 0.001 and 0.56 ± 0.01 pL.cell-1.sec-1, respectively. While the two cancer lines showed the lack of the exocytosis activity. Conclusion: The overall results suggested that both whole cell proteome and kinetic parameter of exocytosis should be considered as characteristics of PBSCs, PBMCs, K562 and K562/adr cells.